VICTIM COMPENSATION IN CRIMINAL JUSTICE SYSTEM: A LEGAL ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
The criminal justice system prioritizes the offender's rights and rehabilitation, often neglecting the victim's needs and suffering. This imbalance threatens the integrity of justice, as victims' rights, particularly regarding compensation, have historically been overlooked, save for minimal provisions in legal codes. Nevertheless, recent judicial trends in India emphasize the necessity of compensatory remedies for victims, highlighting the inadequacies of existing statutory frameworks to address their rights. Crime affects a large number of victims who suffer physical, social, financial, or emotional injury or harm, which needs to be promptly redressed by providing them easy access to justice. In recent decades, there has been a notable shift in criminal law jurisdictions worldwide towards acknowledging the significance of victimization, emphasizing the necessity for victims to be treated with empathy and their dignity upheld. This study will scrutinize the effectiveness and particulars of victim compensation legislation, focusing on the Indian legal framework and recent advancements in victim-centered justice.